MODERN WORLD TRENDS OF PERSONNEL MANAGEMENT SYSTEM DEVELOPMENT IN PUBLIC AUTHORITIES - Fesenko, V. (Pressing Problems of Public Administration, 2019)
The article deals with the current trends in the development of the personnel management system, as one of the main components of the functioning of public authorities in Ukraine. It is shown that further reform, which is happening in Ukraine, requires the introduction and active use in the field of labor relations of public service bodies of new approaches to the development of the personnel management system. The concept of “personnel management system” is characterized and analyzed. The Concept of introduction of the information system of human resources management in state bodies (HRMIS) approved by the order of the Cabinet of Ministers of Ukraine dated 01.12.2017 № 844-p was studied. The review of the structural elements of the personnel management system of public authorities and local self-government, such as: recruiting, evaluation, training, personnel records and motivation. When assessing the state of modern legislation of the public service, it can be noted a significant advantage of the processes of regulation of the public service, in contrast to the local authorities. This phenomenon is related to the draft Law on Amendments to the Law of Ukraine “On Service in Local Self-Government Bodies” vetted by the President of Ukraine. An important aspect of working with the staff is the formation of the innovative potential of the institution and facilitating the implementation of innovative changes. Increasingly, public authorities tend to work with young people, introducing various projects, grants, programs. But, unfortunately, after graduating from specialized higher education institutions, young people are not sure about getting their first job in the public sector, unlike in European countries. Information support of public authorities, as one of the prerequisites for innovative changes, is not at a satisfactory level for personnel accounting. In the context of reforming the public service, there is a tendency to use the principle of declarations in the activities of personnel management services of public authorities. Especially this inclination can be traced in the process of recruiting, evaluating personnel and their motivation. It was emphasized that only when the components of the personnel management system will constantly change, displacing stereotypes, the transformation of the public service is possible.